The Influence Of Interactive Learning Media To Increase Learning Motivation And Learning Outcomes For Early Childhood - sulistyawati, wiwik; Sumartiningsih, Indah; Priatiningsih, Selasih (Program Pasca Sarjana, Universias PGRI Argopuro Jember, 2024)
Specific learning objectives, pedagogical approaches, and the overall learning environment must be taken into account when assessing the impact of interactive media on student motivation and learning outcomes. Learning media have a major influence on children's ability to understand the material presented. This is because the media used is able to provide a real and concrete understanding of the message so that the message conveyed is clearer and deeper The research design used causal quantitative by administering a pretest posttest to young children in Labschool Kindergarten with a number of 25 objects, analysis using the SPSS version 24 program. Based on the summary of the results of the hypothesis test as shown in Table 3 with the results in the first hypothesis test P Value of 0.073 means P> 0.05, in the second hypothesis test P Value of 0.078 means P> 0.05 and in the third hypothesis test P Value is 0.065 means p> 0.05 then in all these tests the zero hypothesis is rejectedThe findings support the hypothesis that interactive multimedia has a positive effect on student motivation and learning outcomes in special subjects on the theme of Introduction to Pancasila in Kindergarten. IKIP PGRI Labschool keyword. interactive learning media, motivation, and learning outcomes